2019
DOI: 10.3389/fpsyg.2019.01952
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Body Image in Internalizing Mental Health Problems in Spanish Adolescents: An Analysis According to Sex, Age, and Socioeconomic Status

Abstract: During adolescence there is a relatively high prevalence of weight problems and eating disorders. Furthermore, body image plays an important role in weight control and eating behaviors as well as in mental health. This study analyses the influence of body mass index, perception of being overweight, and body image satisfaction (BIS) on internalizing symptoms related to mental health in adolescents. In addition, sex, age, socioeconomic status (SES), dieting, and physical activity are taken into consideration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 85 publications
0
28
0
6
Order By: Relevance
“…In addition, our research showed that girls aged 14-16 have significantly lower self-esteem than boys, they consider themselves as more obese, although the BMI level in both sexes was basically the same. Furthermore, clear sex differences were found with regards to problems related to body image in a study by Ramos et al [41]. The results showed that girls, more often than boys, see themselves as fat, feel dissatisfied with their body image, and got on a diet to lose weight/volume.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, our research showed that girls aged 14-16 have significantly lower self-esteem than boys, they consider themselves as more obese, although the BMI level in both sexes was basically the same. Furthermore, clear sex differences were found with regards to problems related to body image in a study by Ramos et al [41]. The results showed that girls, more often than boys, see themselves as fat, feel dissatisfied with their body image, and got on a diet to lose weight/volume.…”
Section: Discussionmentioning
confidence: 94%
“…Children with higher BMI may feel discriminated against due to their image, which could lead them to presenting long-term internalizing symptoms. This is related to an increased awareness and internalization of social attitudes around weight throughout childhood, which is manifested by greater psychological problems in adolescents with a worse body image [41]. Due to the fact that girls have more body image concerns than boys [17], understanding factors uniquely related to the girls' body image discrepancy may be important for developing targeted interventions to address body-related issues and prevent adverse health-related sequelae in this population [22].…”
Section: Introductionmentioning
confidence: 99%
“…Body judgments are characterized by increasing rates of prejudice and discrimination toward overweight people, even if there is an increasing rate of overweight in the population [10]. Mental health is compromised by negative body image aspects, with an increase of psychopathological symptomatology, from depression to eating dysfunctional behaviors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Los mensajes de los medios sociales conllevan una presión que facilita la internalización del ideal delgado (RODGERS, 2016), a través de una constante comparación y monitorización del cuerpo. El cuerpo se valora principalmente en un sentido estético, de tal modo que se contrasta la propia imagen con los prototipos de belleza ideales (RAMOS et al, 2019). Se activa, pues, un proceso reflexivo que evalúa la imagen corporal real respecto a la ideal, y contribuye a la construcción de subjetividades condicionadas por el contexto sociocultural (HOUGHTON, 2019):…”
Section: La Internalización Del Ideal De Cuerpo Delgado Y Consecuenciunclassified
“…Consecuentemente, tienen más probabilidad de experimentar insatisfacción corporal y un mayor deseo de adelgazar, lo que conlleva niveles más bajos de autoestima y confianza en sí mismas. Los problemas vinculados con la insatisfacción corporal pueden relacionarse con episodios de ansiedad físico social (AHADZADEH et al, 2018), siendo la adolescencia uno de los periodos más críticos, con altos índices de preocupación por el cuerpo, especialmente en las chicas (RAMOS et al, 2019).…”
Section: La Internalización Del Ideal De Cuerpo Delgado Y Consecuenciunclassified